A Study on the Actuator Efficiency Behavior of Safety-Related Motor Operated Gate and Globe Valves - Kang, Shin Cheul; Park, SungKeun; Lee, DoHwan; Kim, YangSeok; Kim, DaeWoong (IntechOpen, 2011)
None